Veterinary Interventions to Improve Neonatal Survival on British Beef and Sheep Farms: A Qualitative Study - Adam, Katherine E.; Bruce, Ann; Corbishley, Alexander (Frontiers in Veterinary Science, 2021)
Neonatal lamb and calf deaths are a major issue in UK agriculture. Consistent mortality rates over several decades, despite scientific advances, indicate that socioeconomic factors must also be understood and addressed for effective veterinary service delivery to improve lamb and calf survival. This qualitative study utilised in-depth interviews with vets and farmers to explore the role of the farm vet in maximising survival. Data were analysed using a realist evaluation framework to assess how the mechanisms and context for veterinary service delivery influence survival as the outcome of interest. A lack of a clear definition of neonatal mortality, and the financial, social and emotional impact of losses, are barriers to recording of losses and standardisation of acceptable mortality levels. Despite this, there appears to be an individual threshold on each farm at which losses are perceived as problematic, and veterinary involvement shifts from preventive to reactive. The vet-farmer relationship is central to efforts to maximise survival, but the social and economic capital available to farmers influences the quality of this relationship. Health inequalities are well recognised as an issue in human healthcare and the findings indicate that similar inequalities exist in livestock health systems.